Blocking VEGF by Bevacizumab Compromises Electrophysiological and Morphological Properties of Hippocampal Neurons - Latzer, Pauline; Shchyglo, Olena; Hartl, Tim; Matschke, Veronika; Schlegel, Uwe; Manahan-Vaughan, Denise; Theiss, Carsten (Frontiers in Cellular Neuroscience, 2019)
A hallmark of glioblastoma multiforme (GBM) is neoangiogenesis, mediated by the overexpression of vascular endothelial growth factor (VEGF). Anti-VEGF antibodies, like bevacizumab, prolong progression-free survival in GBM, however, this treatment has been reported to be associated with a decline in neurocognitive function. Therefore, this study focused on the effects of bevacizumab on neuronal function and plasticity. We analyzed neuronal membrane properties and synaptic plasticity in rat hippocampal slices, as well as spine dynamics in dissociated hippocampal neurons, to examine the impact of bevacizumab on hippocampal function and viability. VEGF inhibition resulted in profound impairments in hippocampal synaptic plasticity as well as reductions in dendritic spine number and length. Physiological properties of hippocampal neurons were also affected. These effects of VEGF blockade on hippocampal function may play a role in compromising memory and information processing and thus, may contribute to neurocognitive dysfunction in GBM patients treated with bevacizumab.